Mobile Technology: A Tool to Increase Global Competency Among Higher Education Students - Fox, Evan Michael (International Review of Research in Open and Distributed Learning, 2019)
The advancement of mobile communication technology has contributed to an increasingly interconnected world; however, these devices are not being used as effectively as they could be to improve global challenges. One challenging issue is the lack of preparation college graduates receive to positively contribute to the needs of an interdependent global society. Organizations such as UNESCO, NAFSA, and the OECD have recently declared the critical need for the rising generation to strengthen their global competence, the capacity to examine societal issues and work alongside those of various backgrounds to make a change. School instructors are crucial to preparing students to thrive in multicultural societies and address present day issues. With a staggeringly high rate of cellular device ownership among college students, mobile devices could be optimally positioned as a multi-functional tool ready to assist students in gaining these skills. This paper proposes that, while mobile devices may have contributed to a growing need for globally competent individuals, they can also be used to expand these capacities within university students. The PISA global competency framework developed by the OECD is used to propose how instructors can use mobile technology and research grounded practices to strengthen global competence in students.